On the Job : a history of American work uniforms - Akou, Heather (London : Bloomsbury Publishing, 2024)
Cover -- Halftitle page -- Title page -- Copyright page -- Dedication -- Contents -- Preface -- Acknowledgments -- Abbreviations -- Note on Citations -- 1 Introduction: Why Uniforms? -- Uniforms in the Body of Literature -- Uniformity and the Limits of Fashion Theory -- Standardization in the Late Nineteenth Century -- Purpose and Outline of this Book -- 2 Taking Cues from Royalty: Maids, Porters, and Doormen -- Uniforms for Maids -- Uniforms for Porters -- Uniforms for Doormen -- Conclusion -- 3 Working for Mom and Pop: Barbers, Attendants, and Waitresses -- Uniforms for Barbers -- Uniforms for Theater Attendants -- Uniforms for Gas Station Attendants -- Uniforms for Waitresses -- Conclusion -- 4 Contagion, Caring, and Qualifications: Uniforms in the Healthcare Industry -- Professionalization and Cleanliness, 1870-1920 -- Prestige, Branding, and Fashion, 1920-70 -- Equality, Wellness, and Protection 1970-2020 -- Conclusion -- 5 Government Work: Postal Carriers, Meter Maids, and Park Rangers -- Uniforms for Postal Carriers -- Uniforms for Meter Maids -- Uniforms for Park Rangers -- Conclusion -- 6 Corporate Branding: Receptionists, Bankers, and Baristas -- Uniforms for Receptionists -- Uniforms for Bankers -- Uniforms for Baristas, and Other Fast-Food Workers -- Conclusion -- 7 Adult Entertainment: Sexualized and Embodied Uniforms -- Aesthetic Labor in Adult Entertainment -- Barmaids and Cigarette Girls, 1880-1960 -- Carhops and Topless Dancers, 1920-85 -- Chippendales, Bouncers, and Cocktail Waitresses, 1975-2020 -- Breastaurant Workers, 1980-2020 -- Conclusion -- 8 Envisioning the Future -- Policing Compliance -- Activism for Change -- Expanding Health and Safety -- Opportunities for Further Research -- Notes -- Bibliography -- Index.